Pengaruh Profitabilitas dan Likuiditas Terhadap Nilai Perusahaan dengan Ukuran Perusahaan sebagai Variabel Moderasi - Nadhira Putri, Riza; Mutia Basri, Yesi; Afriana Hanif, Rheny (Akuntansi & Ekonomika, 2025)
The purpose of this study is to examine how profitability and liquidity influence firm value, and how the size of a company can affect the relationship between profitability and liquidity and the value of the company. All energy companies listed on the IDX between 2021 and 2023 were included in this analysis. Secondary data from documents were used as sources of information. Multiple linear regression analysis and MRA were applied in the study using SPSS version 29. The research findings show that profitability affects firm value, but not liquidity. Business size does not significantly affect the relationship between profitability and valuation, but reduces the relationship between liquidity and valuation.